2020
DOI: 10.1017/s1355617720000685
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Change After a Single Season of Head Impact Exposure in Youth Football

Abstract: Objectives: Head impact exposure (HIE) in youth football is a public health concern. The objective of this study was to determine if one season of HIE in youth football was related to cognitive changes. Method: Over 200 participants (ages 9–13) wore instrumented helmets for practices and games to measure the amount of HIE sustained over one season. Pre- and post-season neuropsychological tests were completed. Test score changes were calculated adjusting for practice effects and regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…In a separate investigation using a battery of neuropsychological tests, head impact metrics were significantly associated with impaired performance on a list-learning task among 9- to 10-year-old football players, but no significant relationships were discovered among HIE and the other tests used. 29 That study also found no significant associations between HIE and any measure of neuropsychological function in players aged 11–13 years.…”
Section: Discussionmentioning
confidence: 67%
“…In a separate investigation using a battery of neuropsychological tests, head impact metrics were significantly associated with impaired performance on a list-learning task among 9- to 10-year-old football players, but no significant relationships were discovered among HIE and the other tests used. 29 That study also found no significant associations between HIE and any measure of neuropsychological function in players aged 11–13 years.…”
Section: Discussionmentioning
confidence: 67%
“…However, there is also evidence that HIE can be associated with de cits in both cognitive and behavioral performance following increased levels of HIE. For example, impairments in reaction time, processing speed, memory and learning, balance, impulse control, and attention have been observed in contact sport athletes after one or two seasons, with effects seen across youth, high school, and college level athletes [20,22,23]. Similar results in cognitive measures were also identi ed following exposure to headers performed by soccer players [24,25].…”
Section: Introductionmentioning
confidence: 75%
“…Three players were excluded from statistical analyses at the corresponding assessment time point In previous reports, 9,11,12 we found several outcome measures suggesting a potential association with cumulative impact. On the basis of these results and associations found in other studies, 8,16 we narrowed the list of outcome measures in the current analysis to the 10 most likely to be affected by repetitive head impacts (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive subconcussive head impacts during childhood have been implicated in the development of chronic cognitive and behavioral problems. However, both retrospective 1 , 2 , 3 , 4 , 5 , 6 , 7 and prospective 8 , 9 , 10 , 11 , 12 research studies have yielded conflicting results regarding the association between repetitive head impacts and cognitive and behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation